Deciphering the mysteries of MEG3 LncRNA and its implications in genitourinary cancers - Assal, Reem A.; Rashwan, Hannah H.; Zakaria, Zeina I.; Sweillam, Jana H.; Fouda, Yasmine M.; Abdelhamid, Abdelhamid M.; Youness, Rana A. (Frontiers in Oncology, 2025)
Maternally expressed gene 3 (MEG3), a long non-coding RNA, plays a pivotal role in various biological processes, including tumorigenesis. Aberrant expression of MEG3 has been implicated in several cancers, including genitourinary malignancies. This comprehensive review explores the multifaceted functions of MEG3 in the context of genitourinary cancers through unravelling the molecular mechanisms underlying the influence of MEG3 on cellular proliferation, apoptosis, invasion, and metastasis. Additionally, we discuss the potential clinical implications of MEG3 as a biomarker and therapeutic target in genitourinary cancers. By unraveling the intricate role of MEG3 in these biological processes, this review aims to contribute to the development of novel strategies for the diagnosis and treatment of genitourinary malignancies.